2016
DOI: 10.1158/1078-0432.ccr-16-0609
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Mutations in the MTOR Regulator RRAGC in Follicular Lymphoma

Abstract: Purpose This study was performed to further our understanding of the biological and genetic basis of follicular lymphoma (FL) and to identify potential novel therapy targets. Experimental Design We analyzed previously generated whole exome sequencing data of 23 FL cases and one transformed FL case and expanded findings to a combined total of 125 FL/ 3 t-FL. We modeled the 3D-location of RRAGC-associated hotspot mutations. We performed functional studies on novel RRAGC mutants in stable retrovirally transduce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 48 publications
(43 reference statements)
2
44
0
Order By: Relevance
“…Loss of function mutations in tumor suppressors such as PTEN (Figure 2), or activating mutations in upstream kinases such as protein kinase C delta (PKCδ) or Syk, are the most common causes of mTOR hyperactivity, although various mutations in mTOR itself have also been associated with increased cancer risk [121]. For example, recent studies indicate that up to 17% of follicular lymphoma patients have activating mutations in the mTORC1 regulator RRAGC, enabling constitutive mTORC1 activation independent of amino acid levels [122,123]. Conversely, a polymorphism in the mTOR promoter that leads to decreased mTOR expression has been negatively associated with several different cancer types including acute lymphoblastic leukemia (ALL) [124].…”
Section: Mtor and B Cell Neoplasmsmentioning
confidence: 99%
“…Loss of function mutations in tumor suppressors such as PTEN (Figure 2), or activating mutations in upstream kinases such as protein kinase C delta (PKCδ) or Syk, are the most common causes of mTOR hyperactivity, although various mutations in mTOR itself have also been associated with increased cancer risk [121]. For example, recent studies indicate that up to 17% of follicular lymphoma patients have activating mutations in the mTORC1 regulator RRAGC, enabling constitutive mTORC1 activation independent of amino acid levels [122,123]. Conversely, a polymorphism in the mTOR promoter that leads to decreased mTOR expression has been negatively associated with several different cancer types including acute lymphoblastic leukemia (ALL) [124].…”
Section: Mtor and B Cell Neoplasmsmentioning
confidence: 99%
“…In addition, we detected the mutations p.D367E>D/E, p.R400R>R/W, and p.R471R>R/S ( Figure 1A). We found that clonal mutations in RRAGC and ATP6V1B2 in FL did not occur together, suggesting that the corresponding proteins have overlapping functions in a shared pathway (see below) (24,25).…”
Section: Resultsmentioning
confidence: 93%
“…The spectrum of ATP6V1B2 mutations in 144 FL and 14 transformed FL cells. Recent reports of relatively frequent mutations in the v-ATPase subunit ATP6V1B2 in FL, and mTOR-activating mutations in RRAGC, along with findings of involvement of both proteins in a lysosomal amino acid-sensing pathway to mTOR, prompted us to study the underlying biology of these mutations (18,24,25,27,30). We first determined the frequency and nature of ATP6V1B2 mutations in 144 FL and 14 transformed FL (t-FL) cells using direct Sanger sequencing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding melanocytic neoplasms as they were observed in the proband and his mother, there have been so far only exceptional reports hinting toward an association between these and TSC [23], which could correlate with the relatively significant 10% prevalence of mTOR pathway alterations in melanoma [24]. Similarly, follicular lymphoma has not been reported to be associated with TSC yet, although 10% of follicular lymphomas were reported to display aberrant mTOR pathway activation in one recent study [25,26]. Further probing for mTOR pathway dysregulation and possible TSC gene alterations in both melanocytic lesions and follicular lymphoma may be interesting in that regard.…”
Section: Discussionmentioning
confidence: 99%